Behavior disparities towards blood donation in Sikkim, India - Shenga, Namgay (Medknow Publications, 2008)
BACKGROUND: The aim of the current research was to determine disparities in blood donation motives among the general mass of Sikkim. AIMS: To identify the reasons for people donating and not donating blood voluntarily. SETTINGS AND DESIGN: Population based cross-sectional study in Gangtok, East Sikkim. MATERIALS AND METHODS: PARTICIPANTS: 300 adults by two-stage cluster sampling technique. INTERVENTIONS: None. MAIN OUTCOME MEASURES: Correlates of attitudes towards blood donation. DATA COLLECTION PROCEDURE: The data collection tool used for the study was a pre-tested structured interview schedule by which the principal investigator collected the data using interview technique. STATISTICAL ANALYSIS USED: Percentages and ODDS ratio were used in this study. RESULTS AND CONCLUSIONS: Out of 300 respondents, overwhelming majority (78.7%) of the respondents in the present study felt that people donate blood to save a friend or a relative. On the contrary, minority respondents (46%) were ready to donate blood voluntarily. Only 12.7% of the respondents had ever donated blood while 87.3% had never donated. Among ever donors, gender wise men donors were found to be more; 89% were married, half were from the 30 to 39 years age group. As the per-capita income or level of education increased, so did the percent of blood donors.